Study on compound optimization and performance of pulverized coal wetting suspension agent - Renjun LUO; Xiaonan SUN; Shengyong HU; Shuyun GUO; Bohao ZHANG; Yufei BAI (Meikuang Anquan)
In order to effectively solve the problems of hole collapse, clamping, sticking, waterway blockage and exhaust channel blockage caused by the combination of coal powder and water to form slime in wet drilling operation, three dispersants were optimized and compounded with inorganic salt additives by using the methods of static sedimentation experiment, contact angle experiment and surface tension test experiment of coal powder, and the optimum mass fraction of each reagent was finally determined. The results showed that the optimum ratio of the composite solution was 0.6 % FSJ-01 + 0.8 % NaCl; the wetting suspension dispersion effect of the three dispersants was ranked as FSJ-01 > FSJ-02 > FSJ-03. When the mass fraction of FSJ-01 was 0.6 %, the contact angle reached a minimum of 31.2 °, which was 61.72 % lower than that of water on the surface of pulverized coal. After adding NaCl with a mass fraction of 0.8 %, the surface tension of the composite solution reached a minimum of 26.3 mN/m, which was 64.75 % lower than that of water and 36.17 % lower than that of a single dispersant solution.